2002
DOI: 10.1002/pc.10484
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and strain rate on the tensile behavior of short fiber reinforced polyamide‐6

Abstract: Tensile behavior of extruded short E-glass fiber reinforced polyamide-6 composite sheet has been determined at different temperatures (21.5"C, 50°C 75°C 100°C) and Merent strain rates (O.O5/min, 0.5/min, 5/min). Experimental results show that this composite is a strain rate and temperature dependent material. Both elastic modulus and tensile strength of the composite increased with strain rate and decreased with temperature. Experimental results also show that strain rate sensitivity and temperature sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 5 publications
6
50
0
Order By: Relevance
“…The effect of strain rate and temperature on mechanical behavior of short fiber thermoplastic composites has been reported in the literature [13,25,26]. Wang et al [25] showed that short fiber thermoplastic composite is a strain rate and temperature dependent material.…”
Section: Strain Rate and Temperature Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of strain rate and temperature on mechanical behavior of short fiber thermoplastic composites has been reported in the literature [13,25,26]. Wang et al [25] showed that short fiber thermoplastic composite is a strain rate and temperature dependent material.…”
Section: Strain Rate and Temperature Sensitivitymentioning
confidence: 99%
“…Wang et al [25] showed that short fiber thermoplastic composite is a strain rate and temperature dependent material. Both the elastic 7 modulus and tensile strength of the composite increased with strain rate and decreased with temperature.…”
Section: Strain Rate and Temperature Sensitivitymentioning
confidence: 99%
“…In line with this, several investigations have characterized the thermal and geometric dependency of the material short glass fiber reinforced components under quasi-static [21,12,29], rate [46] and fatigue loading conditions [13] for different fiber orientation angles.…”
Section: Introductionmentioning
confidence: 92%
“…Similar results for the compressive [5] and tensile [5][6][7][8] behavior of the pure polymer under dynamic loading were investigated. Also the tensile strength of short and long glass fiber reinforced polyamide was found to increase with strain rate [7][8][9][10][11]. To the a Corresponding author: ploeckl@lcc.mw.tum.de knowledge of the authors only few attempts were carried out to characterize the dynamic stress-strain response of carbon fiber reinforced polyamide-6 composites.…”
Section: Introductionmentioning
confidence: 99%